2004
DOI: 10.1111/j.1365-2389.2004.00664.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact angle of soils as affected by depth, texture, and land management

Abstract: Water repellency can be a significant factor in soil physical behaviour, but little is known about the depth dependence of the contact angle of field soils. We investigated contact angles and wetting properties as a function of depth for a wide range of agricultural and forest soils in Germany. The agricultural soils ranged from silty to sandy texture (six profiles), and the forest soils ranged from sandy to loamy texture (eight profiles). Contact angles (CA) were measured with the Wilhelmy plate method (WPM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
109
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(121 citation statements)
references
References 36 publications
9
109
0
3
Order By: Relevance
“…In a recent study by Diehl et al (2014) -treated samples could not be reproduced. On the other hand, in a study by Woche et al (2005), analyzing several arable and forest soils ranging from pH 3.0 to 6.8, a significant inverse correlation between CA and pH was found which is in agreement with the general tendency found for the topsoils of this study.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In a recent study by Diehl et al (2014) -treated samples could not be reproduced. On the other hand, in a study by Woche et al (2005), analyzing several arable and forest soils ranging from pH 3.0 to 6.8, a significant inverse correlation between CA and pH was found which is in agreement with the general tendency found for the topsoils of this study.…”
Section: Discussionsupporting
confidence: 75%
“…Bachmann et al (2008) showed that the availability and distribution of water in the soil matrix depends on soil particle wettability. WR occurs in soils of different texture, land use and under a variety of climatic conditions (DeBano, 1981;Doerr et al, 2000;Woche et al, 2005). Mineral surfaces are generally well wettable by water when they are free of any adsorbed organic substances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown (e.g., Blanco-Canqui and Lal, 2009;Goebel et al, 2008;Lachacz et al, 2009;Vogelmann et al, 2013) that soil water sorptivity decreased exponentially with increasing SOM content. Czachor et al (2013), Leelamanie and Karube (2007), Vogelmann et al (2013), and Woche et al, (2005) also reported a non-linear increase of the contact angle with SOM content.…”
Section: Introductionmentioning
confidence: 99%
“…We were aware of the fact that α could differ from 0º. Woche et al (2005) analyzed the dependence between the contact angle and the soil texture and observed small contact angles of 0º to 20º for silty loam soils. Moreover, α strongly depends on water content and probably approached 0º after sufficient infiltration time (Buczko et al, 2006).…”
Section: Wl Methodsmentioning
confidence: 99%